A Numerical Investigation of Electrically-Heated Methane Steam Reforming Over Structured Catalysts - Ambrosetti, Matteo; Beretta, Alessandra; Groppi, Gianpiero; Tronconi, Enrico (Frontiers in Chemical Engineering, 2021)
The use of electric energy as an alternative system to provide heat of reaction enables the cut-off of CO2 emissions of several chemical processes. Among these, electrification of steam methane reforming results in a cleaner production method of hydrogen. In this work, we perform for the first time a numerical investigation of a compact steam reforming unit that exploits the electrical heating of the catalyst support. First, for such unit we consider the optimal thermodynamic conditions to perform the power to hydrogen conversion; the process should be run at atmospheric pressure and in a close temperature range. Then, among possible materials currently used for manufacturing structured supports we identify silicon carbide as the best material to run electrified steam reforming at moderate voltages and currents. The temperature and concentration profiles in idealized units are studied to understand the impact of the catalyst geometry on the process performances and open-cell foams, despite higher internal mass transfer resistances show the best potential. Finally, the impact of heat losses is analyzed by considering different operative conditions and reactor geometries, showing that it is possible to obtain relatively high thermal efficiencies with the proposed methodology.